A longitudinal examination of the consequences of OCBs for individuals in organisations: the moderating roles of percieved organisational support and control - Devonish, Dwayne (2014)
The present thesis was conceptualised and conducted against the backdrop of rapidly emerging research that challenges the conventional depiction of OCBs as positive extra-role behaviours that produce beneficial outcomes to both individuals and organisations. The thesis contends that OCBs may be either beneficial or detrimental to individual performers depending on their perceptions of the psychosocial work environment – i.e. perceived job control and perceived organisational support. Both perceived job control and organisational support have been researched in existing theoretical models and prior research which depict and assess these variables as key moderators in the relationship between work stressors and job strain. Hence, the present thesis hypothesised that both job control and support will moderate the effects of Time 1 OCBs (peer reports of OCB-I and OCB-O) on various individual-level outcomes of job satisfaction, organisational commitment, role ambiguity, role overload, work-family conflict, physical exhaustion and work-related depression measured at Time 2, based on a two-wave longitudinal panel methodological design. This newly proposed moderation model was tested across three interrelated Studies (Study 1, Study 2, and Study 3) in which the first two studies were cross-sectional based on Time 1 and Time 2 data, respectively, and the final study provided a longitudinal version of the same analyses. A direct effects model (where the effects of Time 1 OCBs on the Time 2 outcomes were assessed) and a mediation model (in which role stressors were modelled as mediators between OCBs and job attitudes and health) were also examined, alongside the proposed moderation model.